THE ROLE OF JOB SATISFACTION IN MEDIATING THE INFLUENCE OF QUALITY OF WORK LIFE ON EMPLOYEE PERFORMANCE - Retno Purwani Setyaningrum; Muhamad Ekhsan (Perbanas Institute, 2021)
Employee performance plays an important role in terms of organizational continuity. The success of the entire implementation of work tasks of an organization is largely determined by the existence of quality human resource management. Employee engagement should be more than just a systematic approach, it should be part of the company culture and part of the management philosophy. The purpose of this study was to determine the effect of quality of work-life on performance mediated by job satisfaction. The number of samples in this study was all employees in the production department of an electronics company in the Jababeka industrial area with a total of 72 respondents. This study has been performed using the Smart PLS analysis tool using quantitative methods. The selection is conducted via a Google Form, which completes an online survey. Data analysis techniques used in this research are R-square checks, bootstrapping, route coefficient, and some indirect effects. Results have shown that work-life quality affects employee performance, work-life quality influences job satisfaction, job satisfaction affects employee performance and job satisfaction can help mediate work-life quality on employee performance.